2023
DOI: 10.22603/ssrr.2023-0050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity, Osteopenia, and Scoliosis on Interobserver Reliability of Measures of the Spinopelvic Sagittal Radiographic Parameters

Abstract: We investigated the relationships between patient factors, including obesity, osteopenia, and scoliosis, and the reliability of measures of the spinopelvic sagittal parameters using conventional Xradiography (Xp) and slot-scanning Xp devices (EOS) and examined the differences in interobserver measurement reliability between them. Methods:We retrospectively enrolled 55 patients (52.7 ± 25.3 years, 27 females) with conventional whole-spine Xp and EOS images taken within three months. Patients were classified acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This was often due to the assumption that sagittal radiographs were strictly “sagittal”, leading to the misidentification of one side of the bone as overlapped underneath the other [ 33 ]. The assessors and annotators observed that poor image quality and outlier annotations in the ASIS region were primarily due to patients’ high BMI, which obscured the belly region and complicated the annotation process [ 18 , 31 ]. The literature has also highlighted that pathologic changes associated with femoral heads likely contribute to the low accuracy of femoral head centre identification by estimation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was often due to the assumption that sagittal radiographs were strictly “sagittal”, leading to the misidentification of one side of the bone as overlapped underneath the other [ 33 ]. The assessors and annotators observed that poor image quality and outlier annotations in the ASIS region were primarily due to patients’ high BMI, which obscured the belly region and complicated the annotation process [ 18 , 31 ]. The literature has also highlighted that pathologic changes associated with femoral heads likely contribute to the low accuracy of femoral head centre identification by estimation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this academic debate, clear guidelines for enhancing the accuracy of landmark annotations in clinical settings remain elusive. Research has identified factors such as pathological changes and obesity that obscure certain landmarks [ 17 , 18 ], and different anatomical regions within a single image may exhibit varied error patterns [ 18 , 19 ]. Yet, the impact of suboptimal annotations at a landmark-specific level has not been thoroughly investigated [ 20 ].…”
Section: Introductionmentioning
confidence: 99%